Shadowing Correlation Model for Indoor Multi-hop Radio Link in Office Environment - Fadhli, Mohammad; Handayani, Puji; Hendrantoro, Gamantyo; Mukti, Prasetiyono Hari (JAVA Journal of Electrical and Electronics Engineering, 2016)
Propagation environment greatly affect the performance of wireless network. The excistence of obstacles between transmitter and receiver antennas provide shadowing effect to the transmitted signal. In multi-hop radio link, any link pairs experience shadowing effect that can be correlated if the links have a similar propagation environment. Various studies have shown that correlated shadowing has significant impacts on wireless network’s performance. This paper discusses shadowing correlation of measured two-hop radio link. We propose models that can be used to predict shadowing correlation coefficient of link pairs using deterministic and stochastic formulas. We give an example of the effect of correlated shadowing on the performance of multi-hop radio link in term of its outage probability.